Thymic stromal lymphopoietin and alarmins as possible therapeutical targets for asthma. Issue 6 (December 2021) - Salvati, Lorenzo; Maggi, Laura; Annunziato, Francesco; Cosmi, Lorenzo
Abstract : Purpose of review: Overview of epithelial cytokines, particularly thymic stromal lymphopoietin (TSLP), released by the airway epithelium and the effects of their inhibition on the outcomes of patients with asthma. Recent findings: The epithelial cytokines are early mediators at the top of the inflammatory cascade and are attractive therapeutic targets to prevent exacerbations and improve lung function in patients with type 2 and nontype 2 asthma. Summary: Clinical trials demonstrated that tezepelumab, an anti-TSLP monoclonal antibody, is a promising alternative treatment for asthma that is effective also in nontype 2 asthma. The PATHWAY and NAVIGATOR trials have assessed its effects in improving outcomes on broad clinically diverse populations. The identification of biomarkers will help to predict potential responders and help in asthma treatment personalization.